Europe's quest for the universe : ESO and the VLT, ESA and other projects - Woltjer, Lodewijk, 1930- (EDP Sciences, 2006)
The large European instruments developed for observing the Universe, from the Sun and planets to its most remote reaches, form the principal subject of this book, addresses a wide audience: astronomers and space scientists, students, politicians, amateur astronomers and the educated public.